2014
DOI: 10.1007/s12282-014-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of geminin expression levels in Ki67-high subset of estrogen receptor-positive and HER2-negative breast cancers

Abstract: Geminin-high breast cancers are significantly associated with worse prognosis. Since poorer prognosis was recognized only in the geminin-high group in Ki67-high cancers, we speculate that geminin may be useful for identifying patients in the Ki67-high subset who can avoid unnecessary chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Our data are also in line with studies that showed an association between increased immunohistochemical expression of AURKB and shorter survival in head and neck [31], laryngeal [32], lung [33], hepatocellular [34], biliary tract [35], endometrial [36], and ovarian cancer [37]. Similarly, our results are consistent with association between high GMNN level and shorter survival in breast [38], penile [39], renal cell [40], and other cancers, reviewed by Kapoor [41] and Petropoulou et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…Our data are also in line with studies that showed an association between increased immunohistochemical expression of AURKB and shorter survival in head and neck [31], laryngeal [32], lung [33], hepatocellular [34], biliary tract [35], endometrial [36], and ovarian cancer [37]. Similarly, our results are consistent with association between high GMNN level and shorter survival in breast [38], penile [39], renal cell [40], and other cancers, reviewed by Kapoor [41] and Petropoulou et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…Details of the methods used for immunostaining of pS6, pMAPK and TP53 have been described in a previous report [ 23 ]. For immunohistochemical staining of geminin, a rabbit anti-Geminin antibody (FL-209, diluted 1:200; Santa Cruz Biotechnology, Santa Cruz, CA) was used by following a method described elsewhere [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ki-67 is a nuclear protein associated with proliferation that is an established prognostic biomarker in various human tumor types, including breast cancer, lymphoma and neuroendocrine neoplasia (33)(34)(35). Previously, a high Ki-67 index was reported to predict reduced disease-free and overall survival in intestinal-type gastric cancer (35) and advanced gastric cancer (33).…”
Section: Ihc Score (24) ---------------------------------------------mentioning
confidence: 99%